Thermal and Daylight Evaluation of Building Zones. (November 2015) - Altan, Hasim; Mohelnikova, Jitka; Hofman, Petr
Abstract: An analysis of thermal balance and daylight level in building residential zones is presented in the article. The evaluation is focused on influence of façade thermal insulation layers and multi glass pane windows on reduction of solar gains and daylight level in internal spaces. The evaluation was carried out as a computer simulation study run in software DesignBuilder. The simulation outputs provided information about optimal façade design for energy efficiency and convenient daylighting in buildings under temperate climatic conditions.